Yoga: As an Alternative for Better Health : योगा: एक बेहतर स्वास्थ्य के विकल्प के रूप में - Kumar, Ankit; Poonam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In today’s fast-paced and materialistic world, people are increasingly falling prey to physical and mental health issues such as stress, anxiety, blood pressure, diabetes, and chronic fatigue. Yoga offers a holistic and effective alternative to modern medicine by promoting a balanced lifestyle. Practicing yoga for just 15–20 minutes daily can help individuals manage minor ailments and begin their day with improved energy and calmness. More than a physical exercise, yoga teaches discipline, humanity, tolerance, and self-awareness. In a world fraught with terrorism and communal tensions, yoga serves as a path to inner and global peace. It transcends religion, caste, and nationality, and should not be restricted by religious bias. Yoga brings about physical well-being, mental clarity, and spiritual peace, making it universally beneficial. The celebration of International Yoga Day on June 21 further emphasizes its global relevance and necessity. Abstract in Hindi Language: आज के भौतिकतावादी और व्यस्त जीवन में व्यक्ति मानसिक व शारीरिक रूप से अनेक रोगों से ग्रस्त होता जा रहा है जैसे तनाव, डिप्रेशन, ब्लड प्रेशर, डायबिटीज आदि। ऐसी स्थिति में योग एक समग्र व प्रभावी समाधान के रूप में उभरता है। प्रतिदिन 15–20 मिनट का योगाभ्यास व्यक्ति को छोटी-छोटी बीमारियों से मुक्त कर स्वस्थ व शांत जीवनशैली की ओर ले जाता है। योग केवल शारीरिक व्यायाम नहीं, बल्कि संयम, मानवता, सहिष्णुता और आत्मचिंतन का भी अभ्यास है। आज के समय में जब आतंकवाद और साम्प्रदायिकता जैसी समस्याएं समाज में व्याप्त हैं, योग शांति का मार्ग दिखाता है। यह किसी धर्म, जाति या देश तक सीमित नहीं है और सभी के लिए समान रूप से लाभकारी है। योग से न केवल शारीरिक बल्कि मानसिक और आत्मिक संतुलन भी प्राप्त होता है। यही कारण है कि 21 जून को अंतरराष्ट्रीय योग दिवस के रूप में मनाया जाता है। Keywords: योग, स्वास्थ्य, जीवनशैली, शांति